Real-Time Action Role-Playing Game dengan menggunakan Fuzzy State Automata untuk Mengontrol Pergerakan Enemy - Gary Nathanael Mardianto; Gregorius Satiabudhi; Rolly Intan (Jurnal Infra, 2016)
Video Games are one of the most popular ways for someone to relieve stress or spend their free time. Most of the video game that is available right now can be played in single player. Unfortunately, most of the times when playing video games in single player, people usually get bored quite easily due to the enemy having static patterns as their actions. To overcome this problem, this thesis will be developing a game with an enemy that is not easily predictable.The genre of the game is Action Role-playing Game (ARPG). The Artificial Intelligence involved is made using the Fuzzy State Automata method. Using the Fuzzy State Automata method, the enemy will have to decide which state that it with enter using the input fuzzy sets and act accordingly. The states of the fuzzy state automata in here also have no fixed durations, therefore adding another unpredictability element for the player to deal with.Based on the testing of the Fuzzy State Automata, the artificial intelligence have the ability to react accordingly to its inputs. The Fuzzy State Automata also manages to successfully exhibit the capability of its states to have no fixed durations to make the enemy actions harder to predict.